Mesenteric Cyst in Association with Type-II Jejunoileal Atresia - Rajat Piplani; Samir Kant Acharya; Nidhi Sugandhi; Deepak Bagga (EL-Med-Pub, 2016)
A rare case of type-II jejunoileal atresia with mesenteric cyst in a neonate is being reported here with a brief review of literature.